PENGARUH TINGKAT PEMBIAYAAN PERBANKAN SYARIAH, JUB DAN PDB TERHADAP SBI SYARIAH PERIODE 2003-2013 DENGAN PENDEKATAN ECM - Amalia, Fitri (State Institute of Islamic Studies (IAIN) Salatiga, 2014)
The purpose of this research is to analyze in the short term and long term betweenthree independent variable namely: Islamic Banking Financing, Money Supply(JUB) and Gross Domestic Product (GDP) against Certificates of Bank IndonesiaSharia (SBIS), a period of 2003-2013.The data used in this research is data quarterly(per three months) of march 2003 until september 2013 which are obtainedfrom the monthly reports economic indicators of the Badan Pusat Statistik andmonthly reports macro of Bank Indonesia.This research use Error CorrectionModel approach to see the short-term and long-term relationship between theindependent variable against the dependent variable. The result showed in thelong term only variable Islamic Banking Financing affect Certificates of BankIndonesia Sharia (SBIS ).While in the short-term Certificates of Bank IndonesiaSharia (SBIS ) affected Islamic Banking Financing and Gross Domestic Product.